The Contribution of Arabic In Indonesian Literacy - Syamsu, Pradi Khusufi (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: This article concludes that Arabic has a very significant contribution to shaping the culture of literacy in Indonesia. Arabic influences Indonesian from script to semantic, lexicographic, and grammatical. The Islamic religion which is inseparable from the Arabic language can change the life of Indonesian people who originally oriented art or beautiful temple works to be book-oriented that creates many writings in the form of manuscripts so that the birth of thousands and even millions of manuscripts. For contact with Islam, the Indonesian archipelago population began to recognize and accept rationality, internationality, and universality through writings in the form of manuscripts.This study is a literature study. The author uses two approaches in social sciences that are, historically, to know social, cultural and political phenomena; while the philology approach is used to find out Arabic Jawi manuscripts that are actually rich in unexpected information.Keywords: Arabic, Literacy, Manuscripts, Indonesia, Malay